Hukum Islam di Lingkungan Badan Peradilan Agama Di Indonesia - Dahwadin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The Islamic law that is applied in Indonesia’s religious courts possesses the functions as they are stipulated to be the principles of Islamic law and the legal principles existing in this country. One of the principles in the religious courts is to provide justice according to law and equality. In this principle, the religious courts seek to serve the citizens without discrimination. A literature review with a qualitative approach and content analysis was employed in this study. This research reveals that the values of justice that are worthy to be received by justice seekers can be realized through the investigation in the religious courts which is led by a judicial panel so as to reach a verdict. In addition, the law enforcement is very pivotal to promote legal justice in the Indonesia’s religious courts.